Futures past. economic forecasting in the 20th and 21st century (2020)
Over the last years, the history of economics has received broad attention. As a side-effect of the financial crisis of 2008, much of this research has served a critical purpose: By investigating the history of economic thought, scholars aimed at unveiling how economics helped bringing into being the world of ruthless capitalism we inhabit. Aside from rather “popular” explorations in the history of economic thought, which targeted the entire field of economics (Sedláček 2011; Vogl 2016), the financial crisis also spawned a broad research on the history and impact of economic statistics. Research has especially focused on the history of the Gross Domestic Product (GDP). Scholars have, for example, investigated how the GDP became what has been called “the world’s most powerful number” and how it has helped making economic growth a priority among social scientists and politicians alike (Fioramonti 2013; Speich Chassé 2013; Lepenies 2016; Schmelzer 2016).